Assessing the impact of internal branding on organizational citizenship behavior among hotel employees in Bangladesh - Ashrafi, Dewan Mehrab; Haque, A. K. M. Ahasanul; Sarker, Md. Atiqur Rahman; Chowdhury, Naila Anwar (Pacific Academy of Higher Education & Research University, 2022)
The purpose of the paper is to investigate the relationship between internal branding and organizational citizenship behavior in the hotel industry from the context of Bangladesh. A quantitative approach was employed to gain an understanding regarding the relationship between organizational citizenship behavior and internal branding. The sampling method is characterized by convenience sampling and 253employees from various hotels holding different designations were surveyed through a structured questionnaire. Moreover, factor analysis and regression analysis have been carried out to assess the relationship between internal branding and organizational citizenship behavior. Results indicated that there is a significant positive relationship between organizational citizenship behavior and internal branding. Finding of this study can help the practitioners as well as policymakers of organizations to apprehend the crucial significance of internal branding. Nevertheless, it can assist human resource managers and practitioners in developing effective strategies to enhance organizational performance through organizational citizenship behavior.